2017
DOI: 10.1097/ccm.0000000000002733
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Sepsis Endotypes Among Adults With Sepsis

Abstract: Objective Recent transcriptomic studies describe two subgroups of adults with sepsis differentiated by a sepsis response signature (SRS). The implied biology and related clinical associations are comparable to recently reported pediatric sepsis endotypes, labeled “A” and “B”. We classified adults with sepsis using the pediatric endotyping strategy and the SRS, and determined how endotype assignment, SRS membership, and age interact with respect to mortality. Design Retrospective analysis of publically availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Several groups have published transcriptomic metrics to identify sepsis immune endotypes that may be useful for risk stratification or, eventually, as a companion diagnostic for immune treatments (40,(54)(55)(56)(57)(58). Further, transcriptomic risk stratification is not limited to sepsis; a 63-mRNA metric of blood leukocyte gene expression was recently shown to be accurate in blunt trauma patients to identify those likely to have complicated clinical trajectories (59).…”
Section: Transcriptomics In Risk Stratificationmentioning
confidence: 99%
“…Several groups have published transcriptomic metrics to identify sepsis immune endotypes that may be useful for risk stratification or, eventually, as a companion diagnostic for immune treatments (40,(54)(55)(56)(57)(58). Further, transcriptomic risk stratification is not limited to sepsis; a 63-mRNA metric of blood leukocyte gene expression was recently shown to be accurate in blunt trauma patients to identify those likely to have complicated clinical trajectories (59).…”
Section: Transcriptomics In Risk Stratificationmentioning
confidence: 99%
“…However, when further stratified by age, there was a significant inter action among SRS assignment, endotype assignment and age. Specifically, younger patients co-assigned to SRS1 and endotype A had a substantially higher risk of morta lity, compared with the other possible combinations of age, endotype and SRS assignment 37 . In addition, adults co-assigned to SRS1 and endotype A had the highest rate of mortality, compared with the other three possible co-assignment groups.…”
Section: Wwwnaturecom/nrnephmentioning
confidence: 92%
“…Despite an overlap in pathway enrichment, including T cell and B cell signalling, the overlap in specific gene expression was minimal 35 . In another study, the adult patients from the GAinS cohort were assigned to paediatric endotypes A and B and this analysis demonstrated a relative lack of redundancy across the two classification schemes 37 . Conversely, the MARS investigators demonstrated a substantial overlap between their low-risk Mars3 subset and the SRS2 23 , whereas the Khatri laboratory reported overlap between their inflammopathic cluster and SRS1, as well as between their adaptive cluster and SRS2 (reF.…”
Section: Wwwnaturecom/nrnephmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is possible that single markers may be identified as sufficiently predictive by themselves, it is also possible that groups of genetic, metabolic, and/or clinical features may often occur together, forming groups or “phenotypes” of patients within the broad umbrella of sepsis that may have similar outcomes or treatment response rates. In sepsis and septic shock, phenotypes have recently been described that are associated with variable risk of mortality and would be considered “prognostic” ( 12 , 13 ). In ARDS, phenotypes are described and found to respond variably to different fluid and ventilator management strategies ( 14 ).…”
Section: Challenges In the Evaluation Of Potential Treatmentsmentioning
confidence: 99%